2006
DOI: 10.1111/j.1445-2197.2006.03693.x
|View full text |Cite
|
Sign up to set email alerts
|

Point of Care Testing of Aspirin Resistance in Patients With Vascular Disease

Abstract: A significant proportion of patients taking aspirin do not show laboratory evidence of platelet inhibition and may not be protected from atherothrombotic events. The PFA-100 appears to be a useful tool to screen for both aspirin resistance and excessive aspirin mediated platelet inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…12 Several other PAD studies reported AR prevalence ranging from 9.6% to 27% to 60%. 16,31,32 A 2011 study involving a substudy of 258 PAD patients taking aspirin revealed that 17% had, during 3-month follow-up, consistently demonstrated low response to aspirin when analyzed by platelet function analyzer (PFA). Less than 1% of patients in this study were found to have low aspirin response during 3 months of followup when analyzed with multiple electrode aggregometry and light transmission aggregometry.…”
Section: Ar In Padmentioning
confidence: 99%
“…12 Several other PAD studies reported AR prevalence ranging from 9.6% to 27% to 60%. 16,31,32 A 2011 study involving a substudy of 258 PAD patients taking aspirin revealed that 17% had, during 3-month follow-up, consistently demonstrated low response to aspirin when analyzed by platelet function analyzer (PFA). Less than 1% of patients in this study were found to have low aspirin response during 3 months of followup when analyzed with multiple electrode aggregometry and light transmission aggregometry.…”
Section: Ar In Padmentioning
confidence: 99%
“…Limitations of the PFA‐100 ® include the potential overestimation of the prevalence of aspirin resistance96–100. Wide variability in duplicate testing has also been noted and may exceed 10 per cent101.…”
Section: Resultsmentioning
confidence: 99%